A study the effect of greenhouses- tomato grafting on increasing its tolerance for salinity stress (Journal of Hama University, 2021)
The research was carried out at the Bostan Al-Basha station Lattakia in Sulaiman Agricultural company, in September 2019. The hybrid "Jollanar" was grafted on the rootstock "Defenser". The hybrid and grafted plants were planted in the greenhouse. Three levels of Salinity (0, 50, 100 mg /L of NaCl) were applied. The measurements of plant water status (osmotic pressure and chlorophyll content), yield components (fruit wet weight and diameter, yield kg/m2), and fruit quality parameters (firmness, contents of dry matter, TSS, total acidity, vitamin C, lycopene and Na and Cl contents) were achieved every two weeks.The results showed that salinity led to a significant increase in osmotic pressure, while grafting reduced it (-0.85 MPa). Salinity led to lower plant yield, due to a lower weight and diameter of the fruit, but grafting led to its increase. While, the salinity led to an increase of fruit dry matter, TSS and vitamin C lycopene, Na and Cl content, and to a decrease of firmness, grafting of plant induced an "osmotic adjustment" where osmotic pressure and Na and Cl contents decreased and the contents of chlorophyll, dry matter and TSS increased. The firmness of the fruit and its lycopene content did not affected with grafting.